SEXUAL MATURATION IN CHILDREN POPULATION OF QUILOMBOLA COMMUNITIES, POÇO DAS TRINCHEIRAS, STATE OF ALAGOAS. (Fiep Bulletin - online, 2012)
The human development constitutes the scientific study of how people change as well as the characteristics that remain stable throughout life. In the process of human growth and development, sexual maturation is an important component of transformation, which usually occurs within a sequence more or less constant for each sex. According to Malina (2004), maturation is the term used to describe the biological changes that occur in an orderly way, aiming to develop into adults without the direct influence of external stimuli known, but there are at least partly results from the interaction the organism and its environment. Pubertal changes occurred due to sexual maturation are universal and orderly, but sexual development, however, has large individual variations in the same population group. Although pubertal changes are universal, there are variations among population groups according to age and its incidence rate at which these changes follows. This study characterized the second & THOMAS NELSON (2007) as descriptive of the case study, by analyzing and providing information about the sexual maturation of a remnant of Quilombo communities. The sample consisted of 87 subjects, 01 to 14 years old, 36 boys and 51 girls. To determine the maturational stage of the groups was held adaptation of procedures described by Tanner (1962): AI = Axillary prepubescent. Axillary pubescent AII1 = 1. Axillary pubescent AII2 = 2. AIII = post pubescent. The results showed that 86.2% of respondents are still in pre-pubescent. There was agreement between this study and Tanner (1962) regarding the average age at which each developmental stage was reached
Keywords: Development; sexual maturation; children quilombolas.